Individualization of City Development Strategies: Case of Ekaterinburg and Birmingham) - Bochko, Vladimir Stepanovich; Zacharchuk, Ekaterina Aleksandrovna (Economy of Regions, 2020)
In the XXI century, a strategic approach to the management of individual territories development is becoming increasingly popular worldwide. The creation of scenarios and targets for large urban agglomerations is the most difficult aspect of strategic planning, as the complex structure of economy and social relations generates a variety of interests of different population groups. For such territories, it is inadvisable to use a unified planning template, because the conditions and demands of local communities require individual planning process and approaches. In this context, we decided to compare the development strategies of the Russian city Ekaterinburg and the English city Birmingham. Firstly, they have similar industrial, social and cultural, and demographic characteristics. Secondly, both cities strategic development plans are aimed at increasing their individualization. We demonstrate the necessity and feasibility of individual city development strategies, suggesting a methodology for its creation. Development strategies vary depending on technological and social progress. While technological progress increases the productive forces of cities, social progress ensures individualization of their development strategies by creating specific mentality, sociocultural, ethical and other values. We hypothesise that individual city development strategies depend on the territorial specificity of social progress, based on the needs of a city’s residents. Thus, the emergence of new needs requires updated strategies, adjusting resources in accordance with these new needs. Based on the study and comparison of strategic plans of two cities, we have suggested methodological approaches to the individualization and implementation of city development strategies. We have determined a system of measures ensuring individualization. It includes the establishment of a list of needs, an analysis of the structure and volume of resources, as well as of the ways to satisfy specific needs for achieving the selected goal. For updating a strategy, it is necessary to consider both growing needs and resources to satisfy them. We have concluded that the individualization of city development strategies improves itself through its implementation and focus on satisfying the needs of a specific community, which depend on the characteristics of its social progress. We have proved that the mentality of residents and their social imprinting greatly influence the individualization of cities and their strategies. The scientific, technological and socio- cultural progress increase the individuality of a city. The research results can be used by public authorities and local governments while creating and implementing strategic development documents.